2017
DOI: 10.1177/1715163517701770
|View full text |Cite|
|
Sign up to set email alerts
|

Use of potentially inappropriate medications among ambulatory home-dwelling elderly patients with dementia: A review of the literature

Abstract: Background: Older adults with dementia are at high risk for drug-related adverse outcomes. While much is known about potentially inappropriate medication use in older adults, its prevalence and characteristics among those with dementia are not as well elucidated. We conducted a literature review to examine the prevalence of potentially inappropriate medication use among home-dwelling older adults with dementia. Our secondary aim was to determine the most frequently implicated medications and factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
(139 reference statements)
3
21
0
1
Order By: Relevance
“…A systematic review among older adults with cognitive impairment and dementia reported a varied prevalence of prescription of PIMs of 10.2% to 56.4% across Europe, Australia, and the United States; and the Beers criteria were applied for assessing PIMs in majority of the studies . Another recent literature review reported that among the five studies conducted in ambulatory home‐dwelling patients diagnosed with dementia that used the Beers criteria, the prevalence of PIMs use ranged from 16.2% to 33%, and PIMs were found to be associated with gender, ethnicity, number of medications prescribed, and varied medical conditions . An understanding about the prevalence and determinants of PIMs can help prevent adverse effects and improve the quality of prescribing in this vulnerable age group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review among older adults with cognitive impairment and dementia reported a varied prevalence of prescription of PIMs of 10.2% to 56.4% across Europe, Australia, and the United States; and the Beers criteria were applied for assessing PIMs in majority of the studies . Another recent literature review reported that among the five studies conducted in ambulatory home‐dwelling patients diagnosed with dementia that used the Beers criteria, the prevalence of PIMs use ranged from 16.2% to 33%, and PIMs were found to be associated with gender, ethnicity, number of medications prescribed, and varied medical conditions . An understanding about the prevalence and determinants of PIMs can help prevent adverse effects and improve the quality of prescribing in this vulnerable age group.…”
Section: Introductionmentioning
confidence: 99%
“…16 Another recent literature review reported that among the five studies conducted in ambulatory home-dwelling patients diagnosed with dementia that used the Beers criteria, the prevalence of PIMs use ranged from 16.2% to 33%, and PIMs were found to be associated with gender, ethnicity, number of medications prescribed, and varied medical conditions. 17 An understanding about the prevalence and determinants of PIMs can help prevent adverse effects and improve the quality of prescribing in this vulnerable age group. To our knowledge, this is the first study conducted to evaluate the predictors of prescribing PIMs in older adults with dementia, receiving comprehensive geriatric risk assessments.…”
mentioning
confidence: 99%
“…Polypharmacy (the use of five or more regular medications per day) is widely recognised as a potentially significant contributor to morbidity and mortality in the elderly population [1]. As the proportion of the elderly (80 years and older) population continues to rise, the community burden of medication treated conditions will also increase, along with the risk of adverse drug reactions [2,3]. The geriatric population is especially vulnerable to the effects of polypharmacy due to the age related decline in renal and liver function, which alters drug metabolism and clearance [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Certain drug classes, such as benzodiazepines, antipsychotics and anticholinergics have been well described in the literature to be associated with harm in the elderly population due to age-related increased sensitivity to adverse effects [3,6]. Furthermore, these drug classes are frequently prescribed for elderly patients despite evidence of limited therapeutic benefit [2,3,7,8,9]. While other medications are continued in the elderly beyond the treatment duration required for the primary indication, such as proton pump inhibitors for reflux symptoms and antidepressants for depression [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation